2020
DOI: 10.1021/acsearthspacechem.0c00044
|View full text |Cite
|
Sign up to set email alerts
|

Volatility Change during Droplet Evaporation of Pyruvic Acid

Abstract: Atmospheric water-soluble organic gases such as pyruvic acid are produced in large quantities by 13 photochemical oxidation of biogenic and anthropogenic emissions and undergo water-mediated 14 reactions in aerosols and hydrometeors. These reactions can contribute to aerosol mass by forming 15 less volatile compounds. While progress is being made in understanding the relevant aqueous 16 chemistry, little is known about the chemistry that takes place during droplet evaporation. Here we 17 examine the evaporatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 108 publications
(231 reference statements)
1
13
0
Order By: Relevance
“…Comparable evaporation rates under intermediate and high RH conditions suggest that particle evaporation can be approximated as a liquid-like process for both conditions (i.e., at RH ≥ 40%), in agreement with previous observations of α-pinene SOA particle evaporation (Yli-Juuti et al, 2017;Buchholz et al, 2019;. Additionally, particulate water content may also induce aqueous-phase processes during isothermal evaporation (Buchholz et al, 2019;Petters et al, 2020 SOA particles, we observed strong evidence of such processes under high RH conditions (RH = 80%), which indicates the presence of aerosol-water-induced chemistry (see section 3.3.3).…”
Section: Isothermal Evaporation Behaviour Of Soa Particlessupporting
confidence: 89%
See 1 more Smart Citation
“…Comparable evaporation rates under intermediate and high RH conditions suggest that particle evaporation can be approximated as a liquid-like process for both conditions (i.e., at RH ≥ 40%), in agreement with previous observations of α-pinene SOA particle evaporation (Yli-Juuti et al, 2017;Buchholz et al, 2019;. Additionally, particulate water content may also induce aqueous-phase processes during isothermal evaporation (Buchholz et al, 2019;Petters et al, 2020 SOA particles, we observed strong evidence of such processes under high RH conditions (RH = 80%), which indicates the presence of aerosol-water-induced chemistry (see section 3.3.3).…”
Section: Isothermal Evaporation Behaviour Of Soa Particlessupporting
confidence: 89%
“…Although increasing evidence from laboratory and field observations have suggested the importance of aqueous-phase processes, such reactions are still underrepresented in the existing models because of a lack of fundamental knowledge (McNeill, 2015). While the aqueous-phase processes of simple, typically small carbonyl compounds have been well studied so far (De Haan et al, 2009;Schwier et al, 2010;Yasmeen et al, 2010;Zhao et al, 2012;Zhao et al, 2013;Petters et al, 2020), more studies should investigate the processes involving complex and large molecules with multiple functional groups. To investigate the changes in volatility of SOA particles, we need to compare the number of ions at each desorption temperature between fresh (0.25 h, ℎ ( )) and RTC (4.25 h, ( )) samples collected by on the FIGAERO filter.…”
Section: Atmospheric Implications and Conclusionmentioning
confidence: 99%
“…Uptake of glyoxal has been shown to be enhanced at acidic interfaces (Shi et al, 2020). Changes in droplet size via evaporation or condensation can affect the chemical reactions that take place at the surface via changes in the relative dimensions and chemical environments of the interface and associated bulk phases (Prisle et al, 2012;Djikaev and Ruckenstein, 2019;Petters et al, 2020). The presence of surface-active organic molecules on droplet surfaces can also affect droplet surface tension (Shulman et al, 1996;Prisle et al, 2010b;Bzdek et al, 2020) and morphology (Kwamena et al, 2010) that affect both warm (Sareen et al, 2013;Ovadnevaite et al, 2017) and ice cloud nucleation (Knopf and Forrester, 2011;Perkins et al, 2020) as well as droplet coalescence (Pak et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Particulate water reduces the viscosity and thus enhances particle evaporation with increasing RH. The comparable evaporation rates under intermediate-and high-RH conditions suggest that particle evaporation can be approximated as a liquid-like process for both conditions (i.e., at RH ≥ 40 %), but in addition to this plasticizing effect, particulate water content may also induce aqueous-phase processes during isothermal evaporation (Buchholz et al, 2019;Petters et al, 2020). For the investigated SOA particles, we observed strong evidence of such processes under high-RH conditions (RH = 80 %).…”
Section: Isothermal Evaporation Behavior Of Soa Particlesmentioning
confidence: 60%
“…Although increasing evidence from laboratory and field observations have suggested the importance of aqueous-phase processes, such reactions are still underrepresented in the existing models because of a lack of fundamental knowledge (Mc-Neill, 2015). While the aqueous-phase processes of simple, typically small carbonyl compounds have been well studied so far (De Haan et al, 2009;Schwier et al, 2010;Yasmeen et al, 2010;Li et al, 2011;Zhao et al, 2012Zhao et al, , 2013Petters et al, 2020), more studies should investigate the processes involving complex and large molecules with multiple functional groups.…”
Section: Atmospheric Implications and Conclusionmentioning
confidence: 99%